2020
DOI: 10.1080/26395916.2020.1800821
|View full text |Cite
|
Sign up to set email alerts
|

Coupling spatial pollination supply models with local demand mapping to support collaborative management of ecosystem services

Abstract: Mapping of ecosystem services (ES) is a powerful tool for communication and knowledge sharing about the implications of ecosystem management practices for human wellbeing. This research aimed to show the usefulness of ES mapping for decision-making by combining modelling of ES supply with ES demand mapping in a participatory process with the engagement of relevant stakeholders. We used the ESTIMAP-pollination model to map wild bee abundance and pollination supply in the Sudoeste Alentejano and Costa Vicentina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…By scaling local maps of landscape characteristics, we captured the capacity of mining bees to adapt to local conditions and nest in the most sloped, most south‐facing, barest ground locally available (Potts & Willmer, 1997). Adding a behavioral component to the determination of habitat suitability improves the estimation of pollination services, particularly in the context of the selected modeling framework (Fernandes et al, 2020; Olsson et al, 2015). We believe further consideration of other behavioral components, such as nesting‐site fidelity, can benefit the elaboration of nesting suitability maps and the associated estimation of pollination services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By scaling local maps of landscape characteristics, we captured the capacity of mining bees to adapt to local conditions and nest in the most sloped, most south‐facing, barest ground locally available (Potts & Willmer, 1997). Adding a behavioral component to the determination of habitat suitability improves the estimation of pollination services, particularly in the context of the selected modeling framework (Fernandes et al, 2020; Olsson et al, 2015). We believe further consideration of other behavioral components, such as nesting‐site fidelity, can benefit the elaboration of nesting suitability maps and the associated estimation of pollination services.…”
Section: Discussionmentioning
confidence: 99%
“…Landscape structure thus dictates the delivery of pollination services from wild bees, which has prompted the development of spatially explicit models (SEMs) that account for the contribution of landscape structure when estimating the provision of pollination services (Lonsdorf et al, 2009; Olsson et al, 2015). These models can facilitate the identification of crucial supporting habitats and degraded ecosystems (Zulian et al, 2013), aid policymakers in the design of landscape management strategies (Fernandes et al, 2020; Koh et al, 2016), and ultimately support the evaluation of the economic value of agroenvironmental schemes (Tibesigwa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A study revelledthatOsmia rufa occupied all tubes made of straw and printer sheeting but in plastic straws, the occupation rate was 80% (Wilkaniec & Giejdasz, 2003), in addition, cardboard tubes could reduce the infestation rate of mites (Fernandes et al, 2020). Moreover, (McCallum et al, 2018) found that nest occupation was significantly affected by nest design, with more bees nesting in tubes of milk cartons (71%) than wooden nests, while (Gaston et al, 2005;Guimaraes-Brasil et al, 2020) claimed that there was a nesting preference for bamboo as nest materials.…”
Section: Nesting Materialmentioning
confidence: 99%
“…Gaston et al (2005) found that bamboo tubes were used in more than materials. Fernandes et al (2020) also claimed that cardboard tubes reduce the Table 1 Country, place of installation, maximum occupation rate, type and number of attracted species, materials used in the construction, tube length (cm), diameter (mm), and key results of studies that have used hotels to attract or trap bees (Continued) 5, 8, 13, 20 4,6,8,9 Cavities with diameters between 4 and 8 mm were occupied most often. infestation rate of mites by 81.8%.…”
Section: Bee Hotelsmentioning
confidence: 99%